GAMBARAN SKALA NYERI PADA ANAK DENGAN MENGGUNAKAN SKALA NYERI FLACC SCALE SAAT TINDAKAN INVASIF - Muhammad ' Azari; Safri ' '; Rismadefi ' Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Face, Legs, Activity, Cry, and Consolability (FLACC) scale is a measurement of pain which already has good validity. This scale can be used for children aged 2 months to 7 years old. There are five points that were observed on this scale. The points were facial, foot activity, crying rate, and the capability to be entertained. Each point has a rating of 0-2 with a maximum value of 10. Response of no pain (0), mild pain (1-3), moderate pain (4-6), and severe pain (7-10) so that the scale can be used to assess the scale of pain in children. This research was conducted during the May to June 2015. The aim of this research was to reveal children’s pain scale using FLACC pain scale when invasive procedure in RSUD Arifin Ahcmad was conducted. This research used simple descriptive design. 30 respondents were taken with consecutive sampling technique. The result showed that there was mild pain response in 3 respondents (21,4%), moderate pain response in 7 respondents (50,0%), and severe pain response in 4 respondents (28,6%). According to the resear cher this study recommended that nurses to use FLACC scale to identify the pain scale in children from aged 2 month to 7 years old. so the need consolability can be done as soon as possible. Keywords: : Pain, FLACC scale, invasive procedure